Dreaming Awake. - Byvanck, Valentijn; Kohn, Eduardo; Latour, Bruno; Mello, Luiza; Royoux, Jean-Christoph; Viveiros de Castro, Eduardo (Maastricht : Marres, 2016)
Gonzalez-Foerster, Dominique ; Steegman Mangrané, Daniel ; Zerbini, Luiz
Catalogus naar aanleiding van de tentoonstelling Dreaming Awake, Marres, Maastricht, van 10 maart tot 3 juni 2018
boek